Preparation and activity of Ni-MgO/α-Al2O3 catalysts in the partial oxidation of methane - Doan, Long The Nam (Animo Repository, 2005)
Partial Oxidation is considered to be a promising method to convert natural gas to synthesis gas (“syngas”). Because the reactions involved are difficult to control, it is necessary to investigate appropriate catalysts for this process in order to maximize CH4 conversion and the yield of CO and H2. The catalyst should have high activity and high selectivity as well as high stability. At the same time, it should be available at low cost. Effect of catalyst preparation methods (all slight variants of the precipitation method), Ni/Mg molar ratio and reaction temperature on the performance of Ni/MgO catalysts supported on α-Al2O3 in the partial oxidation of methane to syngas has been investigated. A fixed bed flow system was used to conduct the reaction. The ratio of CH4: O2: N2: He equals to 12: 6: 14: 68 was used in the study. Three catalyst preparation methods produced comparable results in CH4 conversion, CO and H2. Energy Dispersive X-Ray (EDX) analysis and the color of the catalysts after reaction showed that one method was superior due to its higher carbon deposition resistance. Ni/Mg molar ratio affected the reduction temperatures and the performance of the catalysts significantly. When the ratio decreased, activity decreased and reduction temperature increased. The catalyst that has Ni/Mg molar ratio of 1/2 was chosen since it gave the same results as the catalyst that has Ni/Mg molar ratio of 1 in similar conditions. At a Ni/Mg molar ratio of 1/2 and reduction temperature of 8500 C, CH4 conversion and CO selectivity increased (about 65-98% and 65-96%, respectively) when reaction temperature was increased from 600 to 8000 C while H2 selectivity remained almost the same (about 90%). This may be the first time when Ni-MgO/α-Al2O3 catalysts prepared by precipitation method were investigated. The catalyst gave excellent activity and remained stable after 5 h time-on-stream.